The American Republic: Its Constitution, Tendencies, and Destiny - Brownson, Orestes Augustus, 1803-1876 (Salt Lake City, UT : Project Gutenberg, 2000)
"The American Republic: Its Constitution, Tendencies, and Destiny" by O. A. Brownson is an analytical account of the principles guiding the American system of government, written during the mid-19th century. The book delves into the conceptual foundations of the U.S. Constitution, the evolution and nature of governmental authority, and the nation$1 (Bs distinct destiny, particularly in light of the Civil War and the issues of unity and federalism that arose from it. The opening of the text introduces Brownson's ambition to articulate a clearer understanding of the American Republic's constitution and governance. He posits that like individuals, nations undergo stages of self-discovery, and emphasizes the necessity for the United States to recognize its identity, constitution, and political mission. Discussing the implications of the recent Civil War, he argues that this conflict forced a profound reflection on the nation$1 (Bs principles and governance structures. Brownson critiques existing theories of government and state sovereignty, suggesting that misinterpretations have historically plagued American politics, and insists that a deeper comprehension of the foundational doctrines of the Republic is crucial for its future stability and integrity. (This is an automatically generated summary.)s
Introduction -- Government -- Origin of government -- Origin of government, continued -- Origin of government, continued -- Origin of government, concluded -- Constitution of government -- Constitution of government, concluded -- The United States -- Constitution of the United States -- The Constitution, continued -- Secession -- Reconstruction -- Political tendencies -- Destiny: political and religious.
Release date is 2000-01-01
Keywords: Constitutional history -- United States; Reconstruction (U.S. history, 1865-1877); Secession -- United States; United States -- Politics and government -- 1815-1861 -- Philosophy